Multi-Machine Collaborative Positioning Method for Rapid Excavation Complete Equipment - Yang, Wei; Du, Zhangyong; Ji, Pengfei (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
To meet the high-precision positioning needs for multi-machine collaborative operations of rapid excavation equipment, including the bolter miner, crusher, and belt conveyor, a multi-machine collaborative positioning method is proposed. This method uses a laser locator to measure the absolute pose of the bolter miner as the primary reference, and deploys laser ranging and ultrasonic ranging sensor groups on subsequent equipment. Through spatial coordinate transformation and data fusion, the system gets the absolute positions, relative positions, and attitudes of all three machines at the same time. The system setup and collaborative positioning algorithms are explained in detail, and experimental verification is conducted. The results show that the laser ranging subsystem achieves a standard deviation of 4.7~7.3mm for distance measurement within the range of 0.5~1.5m, and a standard deviation of less than 0.16° for attitude angle measurement. The ultrasonic ranging subsystem achieves a standard deviation of 10.5~13.6mm for lateral offset measurement. The positioning accuracy of the proposed method meets the requirements for collaborative operations and can provide technical support for intelligent collaborative control of tunnel excavation equipment.